"THE ROLE OF ESCROW SYSTEMS IN ENSURING SECURE REAL ESTATE TRANSACTIONS IN UZBEKISTAN" (ResearchJet Journal of Analysis and Inventions, 2023)
The theme explores the prospective impact of escrow systems on the security and reliability of real estate transactions in Uzbekistan. It addresses the evolving role of escrow in fostering trust and transparency within the real estate sector. The annotation highlights key elements such as the need for a tailored regulatory framework, the transformative potential of technology, the importance of education and awareness campaigns, the significance of partnerships and collaborations, and the necessity for continuous evaluation and adaptation. The theme emphasizes the strategic integration of escrow systems to shape a secure and efficient real estate landscape in Uzbekistan, underlining its potential to enhance investor confidence and contribute to the overall growth of the real estate sector in the country.